An approach on turbulent flow of pseudo-plastic nanofluids and heat transfer subject to wall slip - Zhang, Jiaojiao; Liu, Chunyan; Zhang, Xuelan; Zheng, Liancun (International communications in heat and mass transfer, 2022)
The purpose of this paper is to study the turbulent flow of pseudo-plastic nanofluids (PPNF) and heat transfer subject to wall slip. Four types of nanoparticles (Fe3O4, CuO, Cu, Ag) are taken into account in carboxymethyl cellulose (CMC)-water-based fluid. The Prandtl mixing length theory is introduced to divide the turbulent boundary layer into two regions: laminar sub-layer and turbulent region. The numerical solutions are obtained by bvp4c technique. Results show that the wall-slip parameter has important influence on velocity and temperature fields, the variations are more intensive in laminar sub-layer. The local friction coefficient decreases for larger wall-slip parameter and smaller fraction of nanoparticles. And the heat transfer is significantly strengthened (in Nusselt number) for smaller wall-slip parameter and larger fraction of nanoparticles. Moreover, for four different nanofluids, the Ag/CMC nanofluid is more conducive to enhance the turbulent heat transfer than other nanofluids. •An approach on turbulent flow and heat transfer of pseudo-plastic nanofluids plate with wall slip are presented.•Prandtl mixing length theory is introduced and numerical solutions are obtained by bvp4c technique.•Results show wall-slip and volume fraction have important influence on velocity and temperature fields.•Local friction coefficient decreases for larger wall-slip parameter and smaller volume fraction.•Heat transfer are significantly strengthened for smaller wall-slip parameter and larger volume fraction.